WOMEN'S ACCOUNTING SOCIETIES. - Frye, Marion A. (The Accounting Review, 1947)
Women in any field or profession have problems and responsibilities that are peculiarly their own. This is especially true in accounting where women form a smaller minority group than in any of the other leading professions or executive groups. To fill the need for work that could not be expected of existing accounting organizations, and was not their responsibility, the American Woman's Society of Certified Public Accounts was organized to advance the professional interest of women certified public accountants. Though of necessity small in membership, it renders a unique service to the profession and to business and industry, as well as to women. To provide an effective medium, the American Woman's Society of Certified Public Accountants organized an affiliate, the American Society of Women Accountants, which through different classifications, provides membership for women who are actively engaged in any phase of accounting, who are instructors or students of accounts or who otherwise have a substantial interest in accounting. Through well-organized and regularly conducted monthly meetings, local chapters in larger cities of the U.S. offer technical and educational programs that are of material aid in improving efficiency of its members, good fellowship and exchange of ideas among women with mutual interests.